The effect of cold water intake on heart rate variability in young women: the co-activation of the sympathetic and parasympathetic branches of the autonomic nervous system - Knežević, Isidora; Tapavički, Borislav; Vukosavljević, Vuk; Maletin, Nemanja; Ivanov, David; Vuletić, Milica; Burić, Dragan; Barak, Otto (Frontiers in Physiology, 2025)
BackgroundHeart rate variability (HRV) reflects the autonomic nervous system’s (ANS) influence on heart rate control. Daily essential activities, such as water ingestion, affect HRV. This study aims to investigate the effect of cold water intake on HRV in young, healthy females.Materials and MethodsFourteen healthy young females participated in the study during the luteal phase of their menstrual cycle. R-R intervals were recorded using an ECG, 5 min before and 35 min after the ingestion. We used LabChart to determine HRV parameters from time (HR, rMSSD, pRR50) and frequency (LF, HF) domains. Data were processed in JASP using repeated-measures ANOVA to compare parameters across five different 5-min ECG segments. A post hoc Bonferroni test revealed specific time points where significant differences occurred.ResultsStatistically significant differences were found in all HRV parameters. The post hoc test revealed differences between pre-ingestion and post-ingestion intervals, while no significant differences were found among the post-ingestion periods. Both branches of the ANS were activated. A statistically significant increase in LF, indicating sympathetic activation, and in rMSSD and pRR50 components, reflecting parasympathetic activity, was observed immediately after cold water ingestion compared to the pre-ingestion period. HF became statistically significantly higher 10 min after cold water ingestion.ConclusionIn young healthy females, the ANS responds coordinately to cold water ingestion, activating both branches to maintain homeostasis, preventing heat loss through sympathetic activation and limiting excessive increases in blood pressure and heart rate via parasympathetic regulation.